Papias as Rhetorician: Ekphrasis in the Bishop's Account of Judas' Death - Zeichmann, Christopher B. (New Testament studies, 2010)
Despite this renewed attention, scholars have avoided situating their analyses of this pericope within the major debates about Papias' work. The question of whether Papias employed the methods of Greek rhetoric sits as the most relevant issue for this discussion. Though many scholars champion rhetorical readings of Papias, detractors contend that they overstate his ostensibly technical vocabulary (e.g., τάξις, συντάσσω, χρεία, διάλεκτος, ἑρμηνευτής in Frag. 2). They generally construe these as Papias' colloquial or historical characterizations of Gospel narratives. Whether and how Papias testifies to source-critical concerns for Synoptic studies—such as the Sayings Gospel Q, a proto-Matthew, and the oral transmission of Jesus' life—depends on their interpretation. Opposition primarily disputes the meaning of individual words in the context Papias provides them, so that his rhetorical forms and flourishes remain relatively unscathed from criticism. Papias' death of Judas has never figured into this discussion, but it nonetheless points in favor of a rhetorical backdrop.